A Política Pública de Assistência Social em conflito com as demandas da população em situação de rua na cidade de São Paulo: um estudo de caso da Tenda Bela Vista - Cordeiro, Diego Borges (2018)
The present dissertation presents results of a "case study", whose analysis is developed from the attendance of a service of public social assistance network of the city of São Paulo and its users-beneficiaries. The research flourishes with the hypothesis that such services do not precisely meet the demands (needs, expectations and aspirations) of its users and that many of these services have been implemented "top-down", that is, services are decided by the political sphere and implementation is merely an administrative effort to find means for the purpose set. Thus, we chose the Espaço de Convivência known as "Tenda Bela Vista", a facility located in the central region of the city and intended for the specific service of the adult homeless population. Through the Tenda we verify if the Public Policy of Social Assistance "lives" or not in conflict with the demands of its public. One of the methodological procedures in this dissertation is to have "attention" to the conflict, justifying the importance of the phenomenon to analyze the confrontations and contradictions in the field of social assistance public policies in the city of São Paulo, believing that it is through conflict that a more accurate reflection is achieved in the face of the public policy implemented. In this way, the methodology used in the field research comprises: participant observation and ethnography, structured interviews through application of forms, analysis of quantitative data, besides the bibliography(ies) of theorists who debate about public policies, of the homeless population and of social assistance policies in Brazil. In the presentation of the results of this research it is pointed out that the public policy of social assistance is exhausted by the demands (which are constantly redefined) of its public-beneficiary and that the conflicts of social assistance interventions are expressed as a phenomenon for their transformations